2016
DOI: 10.1007/s00244-016-0315-3
|View full text |Cite
|
Sign up to set email alerts
|

Medium- and Long-Term Effects of Estrogenic Contaminants on the Middle River Po Fish Community as Reconstructed from a Sediment Core

Abstract: Recent studies showed that endocrine active compounds (EDs) capable to induce fish gonadal histopathologies, plasma vitellogenin and thyroid disruption, are transported by the River Lambro to the River Po, potentially affecting the fish community of the main Italian river. To assess whether fish relative abundance, composition and health were impaired by the River Lambro, a 3-year survey was undertaken in the main river. Results showed that the tributary supports in the River Po a denser fish community (+43 %)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…The very high sensitivity and responsiveness of the oviparous vertebrate liver to estrogens and xenoestrogens have promoted the development of assays using vitellogenin as an informative biomarker for endocrine-disrupting effects of chemicals and effluents. Fishes are the most used test organisms worldwide [ 141 , 187 , 188 , 189 , 190 ] to monitor water quality, contributing to human health in all continents. Interestingly, lizards are also excellent model organisms to monitor contaminating soil xenopestrogens [ 147 , 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…The very high sensitivity and responsiveness of the oviparous vertebrate liver to estrogens and xenoestrogens have promoted the development of assays using vitellogenin as an informative biomarker for endocrine-disrupting effects of chemicals and effluents. Fishes are the most used test organisms worldwide [ 141 , 187 , 188 , 189 , 190 ] to monitor water quality, contributing to human health in all continents. Interestingly, lizards are also excellent model organisms to monitor contaminating soil xenopestrogens [ 147 , 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…Draining one of the most densely inhabited areas in Europe (~1500 inhabitants/km 2 ), this river is a tributary of the main Italian watercourse, the River Po, and contributes significantly to its contamination up to the Adriatic Sea (Viganò et al, 2015). In this regard, previous studies have demonstrated several impacts on the biotic communities exposed to the contaminants transported by the River Lambro (Viganò et al, 2016).…”
Section: Introductionmentioning
confidence: 97%